ChemInform Abstract: Sequential Catalysis for Stereoselective Synthesis of Complex Polyketides. Issue 33 (19th August 2014) - Herkommer, Daniel; Schmalzbauer, Bjoern; Menche, Dirk
Abstract Review: 111 refs.